Vortex method of complex purification from mechanical pollution by impurities of surface and bottom layers of water bodies with use of vortex separators (separators-confusers, cyclones-confusers) - V. I. Kuznetsov; O. A. Sharikov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The method of purification from mechanical pollution by oil, oil products, other materials of surface and bottom surfaces of water bodies with the use of vortex equipment: swirlers, vortex tubes, separatorsconfusers, cyclones is described-confusors, as well as floating vehicles, overpasses, storage tanks, which consists in a consistent separation of the surface layers of polluted water reservoir, de-buoyancy of the bottom layers and, subsequent separation formed, at the same time, the mechanical mixture to the required concentration and combination therein, components, simultaneous enrichment of the resulting semi-finished products and their separation into specific, used in practice materials and substances, transportation of these materials and substances to the packaging for further sale or environmentally friendly disposal. The problem is solved by using the properties of vortex flows of mechanical mixtures, the system application of separators-confusers, cyclones-confusers and creating a new method of complex purification of impurities from surfaces and bottom layers of water bodies by forming counter main flow, swirling flows of mechanical mixtures and managing them in space. The technical result is achieved by improving the technological process of separation of mechanical mixtures, its depth, integrated use of equipment and improve the efficiency of processes. The analysis of literary sources confirms the conclusion that the proposed method has no analogues in the world practice